2021
DOI: 10.1021/acsanm.1c03706
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Ni-NiOx Nanoparticles Distributed on Graphene as Catalysts for the Methanolysis of Ammonia Borane to Produce Hydrogen

Abstract: Ultrasmall Cu/Ni-NiO x nanoparticles (NPs) had been successfully prepared by attaching and growing Ni-NiO x NPs on the surface of Cu NPs and then uniformly dispersed onto graphene (G) surface. High-angle annular dark-field–scanning transmission electron microscopy (HAADF-STEM) characterization confirmed that Ni-NiO x NPs were uniformly distributed on the surface of Cu NPs. The catalytic methanolysis of ammonia borane (AB) proved that Cu/Ni-NiO x NPs possessed high catalytic hydrogen (H2) evolution activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…In order to further improve the catalytic activity of non-noble-metal catalysts, some researchers use nonmetallic elements to regulate non-noble-metal alloys, the electron-acceptor effect is formed between nonmetals and metals, and the catalytic activity is improved by regulating the catalytic activity site of the catalyst. , Kalidindi et al synthesized Co–Co 2 B Ni–Ni 3 B and Co–Ni–B nanocomposites by the reduction of Co 2+ and Ni 2+ ions, the comparison of the rate constants shows the effect of the catalyst following this order: Co–Ni–B > Co–Co 2 B > Ni–Ni 3 B. Zhang et al synthesized a series of Co–B amorphous alloys by liquid phase reduction method, a series of catalysts Co x B 1– x ( x = 0.25, 0.50, 0.75) is synthesized by tuning the n (Co 2+ )/ n (BH 4 – ) to catalyze AB methanolysis for hydrogen production, and the results show that the catalytic activity follows this order: Co 0.75 B 0. 25 > Co 0.50 B 0.50 > Co 0.25 B 0.75 , shown in Figure .…”
Section: Hydrogen Production From Catalytic Ammonia Borane Methanolysismentioning
confidence: 99%
“…In order to further improve the catalytic activity of non-noble-metal catalysts, some researchers use nonmetallic elements to regulate non-noble-metal alloys, the electron-acceptor effect is formed between nonmetals and metals, and the catalytic activity is improved by regulating the catalytic activity site of the catalyst. , Kalidindi et al synthesized Co–Co 2 B Ni–Ni 3 B and Co–Ni–B nanocomposites by the reduction of Co 2+ and Ni 2+ ions, the comparison of the rate constants shows the effect of the catalyst following this order: Co–Ni–B > Co–Co 2 B > Ni–Ni 3 B. Zhang et al synthesized a series of Co–B amorphous alloys by liquid phase reduction method, a series of catalysts Co x B 1– x ( x = 0.25, 0.50, 0.75) is synthesized by tuning the n (Co 2+ )/ n (BH 4 – ) to catalyze AB methanolysis for hydrogen production, and the results show that the catalytic activity follows this order: Co 0.75 B 0. 25 > Co 0.50 B 0.50 > Co 0.25 B 0.75 , shown in Figure .…”
Section: Hydrogen Production From Catalytic Ammonia Borane Methanolysismentioning
confidence: 99%
“…It is also highly soluble in water (33.6 g/100 mL) at room temperature. [5][6][7] Further, AB can quickly release a huge quantity of hydrogen during the Dharman Ranjith Kumar and Samikannu Prabu equal contribution to this work. hydrolytic process in the presence of nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…13 Zheng et al reported that Cu/Ni-NiO x nanoparticles on graphene sheets for AB methonalysis and the nanoparticles possessed higher catalytic hydrogen generation with 17.72 mol H 2 .mol À1 (TOF). 6 Konus et al prepared TiO 2 -supported Ru (0) nanoparticles by in situ reduction process and performed hydrogen production from the AB hydrolysis with a TOF value of 200 min À1 at room temperature. 14 Karatas et al developed Rh (0) nanoparticles on MXene and the catalysts show significant catalytic performance in the hydrogen production with 288.4 min À1 TOF value at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations